Complete mitochondrial genome of Blue-and-yellow Macaw (Ara ararauna): the species morphologically similar to Blue-throated Macaw (Ara glaucogularis). (4th May 2017) - Urantowka, Adam Dawid; Mackiewicz, Paweł; Strzała, Tomasz
Abstract: Six genera of the Arini tribe form morphologically diverse group termed as Macaws. The presence of bare facial area distinguishes them from other members of the tribe. Genera and species of Macaw group differ in pattern of this bare skin as well as in body size. The genus Ara contains eight extant species. Two of them are classified as medium-sized Macaws and other six species are classified as large Macaws. Based on morphological similarities and differences, large Macaw species can be segregated into three pairs according to their plumage coloration. So far, representative mitochondrial genomes were sequenced only for Ara glaucogularis (blue and yellow coloration), Ara macao (predominantly red/scarlet) and Ara militaris (predominantly green) species. Ara ararauna is the second of two Ara species with predominant blue and yellow plumage. Hitherto, close phylogenetic relation of these two species was shown using only ND2 genes or incomplete combined COI/Cytb/ND2 sequences. Therefore, Ara ararauna mitogenome, which was sequenced in this study, will be indispensable to refine the phylogenetic relationships within Macaws group.